Estimating Survival for Elusive Juvenile Pond‐Breeding Salamanders. Issue 3 (2nd January 2020) - Messerman, Arianne F.; Semlitsch, Raymond D.; Leal, Manuel
Abstract : We empirically estimated recapture and survival probabilities for elusive juveniles of 3 complex life cycle salamander species using capture‐mark‐recapture protocols and inference from published salamander vital rates. Estimates of survival were comparable across species and estimation methods, lending support to the use of rigorously estimated vital rate data from ecologically and phylogenetically similar species as place‐holder information in demographic models used to predict population responses to management scenarios for species of conservation concern for which data are sparse. ABSTRACT: Juvenile vital rates have important effects on population dynamics for many species, but this demographic is often difficult to locate and track. As such, we frequently lack reliable estimates of juvenile survival, which are necessary for accurately assessing population stability and potential management approaches to conserve biodiversity. We estimated survival rates for elusive juveniles of 3 species, the ringed salamander ( Ambystoma annulatum ), spotted salamander ( A. maculatum ), and small‐mouthed salamander ( A. texanum ), using 2 approaches. First, we conducted an 11‐month (2016–2017) mark‐recapture study within semi‐natural enclosures and used Bayesian Cormack‐Jolly‐Seber models to estimate survival and recapture probabilities. Second, we inferred the expected annual juvenile survival rate given published vital rates for pre‐metamorphic and adult ambystomatids assuming stable population growth. For all 3 species, juvenile survival probabilities were constant across recapture occasions, whereas recapture probability estimates were time‐dependent. Further, survival and recapture probabilities among study species were similar. Post‐study sampling revealed that the initial study period median estimate of annual survival probability (0.39) underestimated the number of salamanders known alive at 11 months. We therefore appended approximately 1 year of opportunistic data, which produced a median annual survival probability of 0.50, encompassing salamanders that we knew to have been alive. Calculation from literature values suggested a mean annual terrestrial juvenile ambystomatid survival probability of 0.49. Similar results among our approaches indicated that juvenile survival estimates for the study species were robust and likely comparable to rates in nature. These estimates can now be confidently applied to research, monitoring, and management efforts for the study species and ecologically similar taxa. Our findings indicated that similarly robust vital rate estimates for subsets of ecologically and phylogenetically similar species can provide reasonable surrogate demographic information that can be used to reveal key factors influencing population viability for data‐deficient species. © 2020 The Wildlife Society.